Treatment of steroid-unresponsive optic neuritis with plasma exchange - Sharon Roesner; Richard G. Appel; J. Gbadamosi; Roland Martinꝉ; Christoph Heesen (2011)
Until now, the significance of plasma exchange (PE) as a treatment for steroid-unresponsive optic neuritis (ON) is still unclear because placebo-controlled and larger studies are missing. We report our experience with 23 patients treated by PE due to steroid-unresponsive ON.Patients were admitted to the University Medical Center Hamburg-Eppendorf between 2006 and 2010 with a visual acuity of <50% on the affected eye following steroid treatment. Ten patients suffered from RR-MS, one from neuromyelitis optica, and 12 patients developed ON as a clinically isolated syndrome. Routinely, they were treated with five cycles of PE. Visual acuity was measured before and directly after PE and during follow-up (first follow-up after 50 days, second follow-up after 174 days).Altogether, 70% of our patients improved after PE, 69% of them showed a good or very good response to therapy. Patients who improved well after PE (n = 11) showed a mean visual acuity of 16% before PE compared to 45% immediately after PE and 60% at the first follow-up. No serious adverse events occurred.To our knowledge, our study is the largest case series of patients with steroid-unresponsive ON treated with PE. Based on our experience, we conclude that PE is an important treatment option for patients with steroid-unresponsive ON although placebo-controlled studies are missing until now.